Un científico en la política peruana. Mariano H. Cornejo, la república aristocrática y la patria nueva, 1895-1920 - Peralta, Víctor (Revista Complutense de Historia de América, 2001)
Through the study of the political life of sociologist Mariano H. Cornejo I try to revalue the strategic role that this important person occupied in the trajectory of the Peruvian party systems between 1895 and 1919. Also this study analyses his participation in the making of the authoritarian ideology of Augusto B. Leguia’s Patria Nueva since 1920. This sociologist subordinated all his political interpretations to his positivist ideology.
Keywords: Peru; political history; intellectuals; political parties; positivism; authoritarianism